Internship and Monograph reports entitled ”Ubiquitin Specific Protease 7 (USP7) Inhibitors as New Agents in Cancer Treatment" - Mendes, Rui Filipe Matias (2020)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia